Invigoration of Kamba Local Rice Seeds Using Rhizobacteria Biopriming In The Test Method of Established Rolled Paper In Plastic (UKDdp) - Sudewi, Sri; Saleh, Abdul Rahim; Herwati, Andi (AGRIUM: Jurnal Ilmu Pertanian, 2026)
The quality of local rice seeds among farmers is low because they generally use harvested seeds from previous crops. One technique that can be done is seed invigorisation using rhizobacteria biopriming technique. The aim of this study was to determine the response of dormant Kamba local rice seeds to rhizobacterial biopriming treatment in increasing the viability and vigor seeds. The research method used a Completely Randomized Design (CRD) with treatments consisting of Control (B0), Biopriming isolate B1; B2; B3; B4; B5; B6; B7; B8; B9; B10; B11; B12; B13; B14. Each treatment was repeated three times to obtain 45 experimental units. Each experiment used 40 seeds for a total of 1800 seeds. Variable observations of seed viability and vigor were carried out with the parameters of germination (%), maximum growth potential (%), simultaneity of growth (%), vigor index (%) and T50% (days). The results showed that biopriming with rhizobacterial isolates using the Rolled Paper Established in Plastic (UKDdp) method had a significant effect on increasing viability and vigor and breaking dormancy of local Kamba rice seeds. The biopriming treatment of KLE25 isolate was effective in increasing germination rate (97.50%), maximum growth potential (99.17%), growth simultaneity (49.17%), vigor index (32.50%) and T50% (4 days) when compared to without biopriming (control).